The burden of testicular cancer from 1990 to 2019 in the Middle East and North Africa region - Safiri, Saeid; Hassanzadeh, Kamaleddin; Janbaz Alamdary, Sina; Mousavi, Seyed Ehsan; Nejadghaderi, Seyed Aria; Sullman, Mark J. M.; Naghdi-Sedeh, Nima; Kolahi, Ali-Asghar (Frontiers in Oncology, 2023)
Background: The incidence rate of testicular cancer has increased in many countries over the last few decades. This study aimed to report the burden of testicular cancer in the Middle East and North Africa (MENA) region, between 1990 and 2019, by age and socio-demographic index (SDI). Methods: Data on the incidence, death, and disability-adjusted life-years (DALYs) attributable to testicular cancer were retrieved from the Global Burden of Disease study 2019. The counts and age-standardised rates (per 100,000) were presented, along with their corresponding 95% uncertainty intervals (UIs). Results: In 2019, testicular cancer had an age-standardised incidence rate of 1.4 per 100,000 population and an annual death rate of 0.1 in MENA, which have increased by 244.0% and 2.6%, respectively, since 1990. In 2019, the number of DALYs due to testicular cancer was 31.1 thousand, with an age-standardised DALY rate of 5.0, which was 2.8% higher than in 1990. The highest incidence rate in 2019 was found in the 1-4 age group. In addition, compared to 1990, in 2019 the MENA/Global DALY ratio was higher than one in the 1-14 year age groups. During the period 1990 to 2019, the burden of testicular cancer steadily increased with increasing SDI, except for a decrease at an SDI of 0.8. Conclusions: The burden of testicular cancer in MENA has significantly increased over the past three decades.